Juridical Implications for Notaries Who Are Declared Bankrupt in the Concept of Legal Certainty - Nainggolan, Nazarudin (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to determine and analyze the juridical implications of notaries who are declared bankrupt in the concept of legal certainty and the legal position of deeds that have been made by notaries and declared bankrupt. The research approach method used in this thesis is qualitative analysis with a normative juridical approach with legislation as the basic basis for research and analysis based on library study materials as well as literature and other scientific works. The type of data used in this research is primary legal material which includes: the Constitution of the Republic of Indonesia of 1945, Law No. 2 of 2014 Amendments to Law No. 30 of 2004 concerning the Position of Notaries, the Civil Code and Secondary Legal Material which includes: Scientific works, legal journals, research results and tertiary legal materials including: legal dictionaries, encyclopedias, print and electronic media. The data analysis method used in analyzing the data is qualitative analysis. The results of the research show that as a result of the law a notary being declared bankrupt will lose all rights under his authority and will not have the obligation to carry out services for making authentic deeds, agreements and other legal acts and deeds that have been made by the Notary, still have permanent legal force and cannot be degraded into a deed that hand because there was no error in making the deed. Keywords: Bankruptcy; Certainty; Notary.